2016
DOI: 10.1080/15332985.2016.1173160
|View full text |Cite
|
Sign up to set email alerts
|

Managing physical and mental health conditions: Consumer perspectives on integrated care

Abstract: Background Despite the growing trend of integrating primary care and mental health services, little research has documented how consumers with severe mental illnesses manage comorbid conditions or view integrated services. Objectives We sought to better understand how consumers perceive and manage both mental and physical health conditions and their views of integrated services. Methods We conducted semi-structured interviews with consumers receiving primary care services integrated in a community mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Literature has shown that patients want integrated care and shared knowledge [ 7 ]; that they view general practice as important for continuity of care, and that they value GPs’ listening skills [ 10 ]. This corresponds to the findings in the present study, where collaboration was hampered by the lack of information flowing from psychiatry to general practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature has shown that patients want integrated care and shared knowledge [ 7 ]; that they view general practice as important for continuity of care, and that they value GPs’ listening skills [ 10 ]. This corresponds to the findings in the present study, where collaboration was hampered by the lack of information flowing from psychiatry to general practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several research projects have tried to unravel this problem and to find solutions [1,4,5]. Focus has been on collaborative work between medical and psychiatric care, either based in the hospital system [6][7][8][9] or involving the professionals from the primary health care sector [10][11][12][13]. Most of these programmes have shown disappointing results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the growing body of scientific evidence relating to integrated care and its implications, few studies 12 13 have summarised patients’ perspectives and expectations of integrated care. There is a lack of comprehensive understanding of what older people themselves consider to be integrated care, what does it mean to them and what do they expect.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers in that study discussed the challenges of coordinating their care among multiple providers. Among individuals with serious mental illness already receiving care in a reverse-integrated system, Rollins and colleagues (28) found that consumers specifically cited convenience, friendly staff, and increased collaboration among providers as features fueling a positive view of the care setting. Given the engagement difficulties noted in realworld pilot studies of reverse-integrated systems, there is a critical need to build on this evidence base in order to understand how to tailor reverse-integrated and reversecolocated models to engage consumers.…”
mentioning
confidence: 99%